A biomonitor of heavy metals on ruderal habitats in Turkey - diplotaxis tenuifolia (L.) DC. - Ozturk, M.; Sakcali, S.; Celik, A. (Universiti Kebangsaan Malaysia, 2013)
Diplotaxis tenuifolia is a medicinally important perennial plant species, distributed widely alongside the roads in Turkey. The samples were collected from 54 sites, including highways, sideways, industrial areas, urban centres and rural environs. Both the plant and soil samples were analysed to determine the concentrations of different metals using AAS. The results showed that in the soil samples copper and lead were highest near highway 45.533 and 2.865 mg/kg, respectively; but lowest values of copper were determined around industrial areas (3.514 mg/kg), latter however showed higher concentrations of cadmium (0.726 mg/kg) and iron (82.766 mg/kg). The lead as well as iron were the lowest around sideways 1.917 mg/kg and 54.073 mg/kg, respectively, whereas chromium concentrations in the soils were highest near sideways (18.397 mg/kg) and lowest around industrial areas (0.182 mg/kg). The sideways showed very low nickel concentrations (0.271 mg/kg), as compared to the rural areas which had higher nickel concentrations (0.726 mg/kg). No cadmium was detected in the urban soil samples. In the plants copper and chromium were higher in the urban areas 50.130 and 0.238 mg/kg, respectively. The former was lowest around sideways (32.377 mg/kg) and latter around highways (0.114 mg/kg). Both nickel and cadmium were higher in the samples from industrial areas 0.238 and 0.016 mg/kg, respectively. Their values around the highways were lowest 0.182 and 0.005 mg/kg. The samples from urban sites revealed highest values of lead (3.474 mg/kg) and iron (61.304 mg/kg), but the values of lead were lowest around sideways (2.420 mg/kg) and those of iron in the vicinity of industrial areas (20.600 mg/kg). All these findings depict that there is some aerial deposition of these metals on the leaves. A significant correlation is seen between the plants and the soils.